2018
DOI: 10.3390/educsci8030129
|View full text |Cite
|
Sign up to set email alerts
|

Development, Uptake, and Wider Applicability of the Yo-yo Strategy in Biology Education Research: A Reappraisal

Abstract: Heredity is a biological phenomenon that manifests itself on different levels of biological organization. The yo-yo learning and teaching strategy, which draws on the hierarchy of life, has been developed to tackle the macro-micro problem and to foster coherent understanding of genetic phenomena. Its wider applicability was suggested and since then yo-yo learning seems to be noticed in the biology education research community. The aim of this paper is to reappraise yo-yo thinking in biology education research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 39 publications
2
51
0
2
Order By: Relevance
“…Only three of the articles analysed in this review mention such challenges. [51] reviewed cases of the Yo-Yo teaching and learning strategy (Yo-Yo-thinking). In their study, they reviewed the articles regarding difficulties concerning the implementation of YoYo-thinking.…”
Section: Research Question 4: How Do the Authors Describe The Challenmentioning
confidence: 99%
See 4 more Smart Citations
“…Only three of the articles analysed in this review mention such challenges. [51] reviewed cases of the Yo-Yo teaching and learning strategy (Yo-Yo-thinking). In their study, they reviewed the articles regarding difficulties concerning the implementation of YoYo-thinking.…”
Section: Research Question 4: How Do the Authors Describe The Challenmentioning
confidence: 99%
“…In their study, they reviewed the articles regarding difficulties concerning the implementation of YoYo-thinking. Knippels and Waarlo [51] found few descriptions of challenges. Only one of the articles Knippels and Waarlo [51] reviewed offers insights into challenges: Van Mil et al [14] reported that their teaching approach was difficult for teachers.…”
Section: Research Question 4: How Do the Authors Describe The Challenmentioning
confidence: 99%
See 3 more Smart Citations